2012
DOI: 10.6061/clinics/2012(12)11
|View full text |Cite
|
Sign up to set email alerts
|

Standard surgical treatment for benign prostatic hyperplasia is safe for patients over 75 years: Analysis of 100 cases from a high-volume urologic center

Abstract: OBJECTIVES:In this study, we aimed to determine the complications of standard surgical treatments among patients over 75 years in a high-volume urologic center.METHODS:We analyzed 100 consecutive patients older than 75 years who had undergone transurethral prostatic resection of the prostate or open prostatectomy for treatment of benign prostatic hyperplasia from January 2008 to March 2010. We analyzed patient age, prostate volume, prostate-specific antigen level, international prostatic symptom score, quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
3
12
0
6
Order By: Relevance
“…As Marmiroli et al [ 11 ] reported, the prevalence of hypertension, a history of surgery, and other complications such as cardiovascular disease and neurologic disease increased in older patients significantly. Several baseline characteristics of the patients were significantly different among the 4 groups, including the presence of hypertension and urinary retention, total prostate volume, transitional zone volume, mean ASA score, and the number of patients using anticoagulation medications, which increased with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Marmiroli et al [ 11 ] reported, the prevalence of hypertension, a history of surgery, and other complications such as cardiovascular disease and neurologic disease increased in older patients significantly. Several baseline characteristics of the patients were significantly different among the 4 groups, including the presence of hypertension and urinary retention, total prostate volume, transitional zone volume, mean ASA score, and the number of patients using anticoagulation medications, which increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with those previously reported [ 12 ]. Oral anticoagulant use independently affects TURP outcome, with longer hospital stay, and higher rates of bleeding, blood transfusion, late hematuria, and thromboembolic events [ 11 ]. As Mmeje et al [ 10 ] reported, the overall blood transfusion rate was highest in patients ≥80 years (11%) who underwent HoLEP.…”
Section: Discussionmentioning
confidence: 99%
“…98,99 A study combining a follow-up of greater than 15 years after TURP, stated satisfaction rates of 79% in regards to micturition. 100 Due to the significance of quality of life domain in urology field, a targeted health education program and training must be taken into consideration due to some of the healthcare professionals have a lack of knowledge related to HRQOL assessment, analysis, and interpretation. 101 It is therefore paramount for urological nurses to communicate and provide an intensive consultation relating to the realistic expectations of quality of life aspect to those having a his- 103 This approach should also be incorporated in a TURP nursing care plan, and patients along with their families must participate-particularly in decision-making relating to the finest interventions.…”
Section: Emotional and Psychological Factorsmentioning
confidence: 99%
“…Procedures involve transurethral resection of the prostate (TURP) and holmium laser enucleation of the prostate (HoLEP), 19 of which TURP has been the benchmark therapy for BPH. 3,17 TURP involves the resection of the abnormally enlarged prostate tissue and involves the use of a wire loop that is heated by an alternating electrical current. 2 Typically, a rigid endoscope is inserted through the urethra of the patient and the prostate tissue is resected under endoscopic observation.…”
Section: Introductionmentioning
confidence: 99%